Hubungan Antara Indeks Massa Tubuh dan Kadar Hemoglobin pada Remaja Putri - Dwi Eni Danarsih; Arum Margi Kusumawardani; Ristiana Eka Ariningtyas (Jurnal Indonesia Sehat, 2023)
Background:  Obesity in adolescents is a global health problem with cases increasing, especially in the Asian region. Obesity has a broad impact on health Obesity in adolescents is a risk factor for obesity in adulthood and is known to contribute to hematological changes, including hemoglobin (Hb) levels. Objective: to determine the relationship between Body Mass Index (BMI) and hemoglobin levels in  female adolescents. Methods: This research is a correlation study between BMI values and Hb levels. Data collection on BMI and Hb levels will be carried out on adolescent subjects from the Bantul and Yogyakarta regions. The number of research subjects was 34 young women. Results: The average BMI for young women is 23.4 kg/m2. The average Hb level is 13 gr/dL with the highest value being 15 gr/dL and the lowest being 9 gr/dL. The correlation coefficient between BMI and Hb levels was 0.013 with a p value of 0.942. Conclusion: There is no relationship between BMI values and hemoglobin levels in female adolescents.